Adenosine modulates hypoxia-induced responses in rat PC12 cells via the A(2A) receptor - Kobayashi, Shuichi (Blackwell Science Inc, 1998)
1. The present study was undertaken to determine the role of adenosine in mediating the cellular responses to hypoxia in rat phaeochromocytoma (PC12) cells, an oxygen-sensitive clonal cell line. 2. Reverse transcriptase polymerase chain reaction studies revealed that PC12 cells express adenosine deaminase (the first catalysing enzyme of adenosine degradation) and the A(2A) and A(2B) adenosine receptors, but not the A(1) or A(3) adenosine receptors. 3. Whole-cell current- and voltage-clamp experiments showed that adenosine attenuated the hypoxia-induced membrane depolarization. The hypoxia-induced suppression of the voltage-sensitive potassium current (I(K(V))) was markedly reduced by adenosine. Furthermore, extracellularly applied adenosine increased the peak amplitudes of I(K(V)) in a concentration-dependent manner. This increase was blocked by pretreatment not only with a non-specific adenosine receptor antagonist, 8-phenyltheophylline (8-PT), but also with a selective A(2A) receptor antagonist, ZM241385. 4. Ca(2+) imaging studies using fura-2 acetoxymethyl ester (fura-2 AM) revealed that the increase in intracellular free Ca(2+) during hypoxic exposure was attenuated significantly by adenosine. Voltage-clamp studies showed that adenosine inhibited the voltage-dependent Ca(2+) currents (I(Ca)) in a concentration-dependent fashion. This inhibition was also abolished by both 8-PT and ZM241385. 5. The modulation of both I(K(V)) and I(Ca) by adenosine was prevented by intracellular application of an inhibitor of protein kinase A (PKA), PKA inhibitor fragment (6–22) amide. In addition, the effect of adenosine on either I(K(V)) or I(Ca) was absent in PKA-deficient PC12 cells. 6. These results indicate that the modulatory effects of adenosine on the hypoxia-induced membrane responses of PC12 cells are likely to be mediated via activation of the A(2A) receptor, and that the PKA pathway is required for these modulatory actions. We propose that this modulation serves to regulate membrane excitability in PC12 cells and possibly other oxygen-sensitive cells during hypoxia.